The Story of Prophet Zakariyya (AS) - "Khan, Saniyasnaian" (China; Goodword book, 2024)
This enchantingly illustrated board book delightfully introduces children to the inspiring life and teachings of Prophet Zakariya (A.S). Through simple and engaging language, young readers learn about his faith, patience, and devotion to Allah. The story highlights important values such as trust in Allah$1 (Bs mercy and the power of prayer. Each page is brought to life with bright, colorful illustrations that capture children$1 (Bs imagination. Designed especially for toddlers and preschoolers, the sturdy board book format is perfect for little hands and repeated reading. This book offers a meaningful way for families to share the lessons of Prophet Zakariya$1 (Bs life and nurture early spiritual growth.s
Keywords: Prophets story